Analisis Tindak Tutur Ilokusi dalam Film Mariposa Karya Alim Sudio - Zahra Oktiawalia, Rahmita; Ariesya, Retno Oktafiayu; Husnul Khotimah, Anis Marfuah; Setiawan, Kodrat Eko Putro; Utomo, Asep Purwo Yudi (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2022)
Speech act is one of the analyzes of pragmatic studies that examines language and relates to aspects of its actual use. One type of speech act is illocutionary speech act. There are many kinds that can be studied using illocutionary speech acts, one of which is speech acts in films. The background of this research is because the film Mariposa by Alim Sudio found many sentences or utterances that refer to the type of illocutionary speech act. This study aims to analyze and describe the types and forms of illocutionary speech acts that exist in the speech of the characters in the Mariposa film. The research method in this study used a pragmatic and qualitative research form. Based on data analysis, it was found that in Alim Sudio's Mariposa film there are 50 illocutionary speech acts which include representative speech acts, directive speech acts, expressive or evaluative speech acts, commissive speech acts, and declaration speech acts. The representative speech acts in Alim Sudio's Mariposa film consist of fifteen utterances. There are sixteen directive speech acts in Alim Sudio's Mariposa film. There are eleven expressive or evaluative speech acts in the Mariposa film by Alim Sudio. There are four commissive speech acts in Alim Sudio's Mariposa film. There are four speech acts of declaration in Alim Sudio's Mariposa film. Then, the benefits of research on illocutionary speech acts in Alim Sudio's film Mariposa are to have a critical understanding, broaden horizons, increase knowledge and knowledge from analyzing illocutionary speech acts through films.